Low-energy design strategies for retrofitting existing residential buildings in Cyprus. Issue 5 (11th July 2018) - Ozarisoy, Bertug; Altan, Hasim
Abstract : Problems on mass housing estates are currently a topic for research on energy and policy interventions in Cyprus. Modernist urban detached/semi-detached and suburban row houses often have insufficient green areas and lack consideration of the climatic features of the building site where the neighbourhoods are designed without concern for urban planning laws and regulations. These purpose-built residential building stock models represent 30% of the existing building stock. This research primarily investigates the potential of particular design interventions in detached two-storey houses in a Mediterranean climate in order to reduce the need for fossil fuel to heat and cool the houses. The aim of this study is to develop and test feasible retrofit strategies aimed at optimising the energy performance of the existing residential buildings. To accomplish this, the study first examines the energy performance of a building before and after the retrofitting phases as base case scenario models. The Autodesk Revit 2017 plug-in Green Building Studio energy performance analysis software was used for simulation of the adapted energy-efficient retrofit measures. This study also outlines the results from the prototype analysis to demonstrate the difference between a retrofitted building and the existing state of a building in their respective energy use impacts.